Up and out of poverty - Xi Jinping (Beijing Foreign Languages Press Co. Ltd, 2016)
As the first personal monograph of General Secretary Xi Jinping, this book faithfully records his practices of carrying out the party's line, policies and regulations, building well-off society in an all-around way and promoting the cause of socialism with Chinese characteristics; shows his key thoughts in economic, political, cultural, social, ecological civilization construction and Party building; reflects his firm political stand, value pursuit and thinking style, thus of great theoretical value and practical value.
How can a weak hatchling bird be the first to fly? - thoughts from inspecting the nine counties of Ningde September 1988 -- "economic chorus" September 1988 -- The basic proficiency of officials - maintaining close ties with the people January 1989 -- The glories of Ningde - thoughts on cultural progress January 1990 -- Clean government is the historical mission of communists February 1990 -- A chat about entering public service March 1990 -- the nature of a secretary's work- an intimate discussion with officials in prefecture and county general offices March 1990 -- Water droplets drilling through rock March 1990 -- Always keeping the people in mind - on handling petition work in the new situation April 1990 -- Seize new opportunities October 1988 -- Thoughts on economic development in Ningde prefecture January 1989 -- Work for the interests of the local people with each term in office January 1989 -- Journalism: mastering the fundamentals May 1989 -- Correctly manage six relationships in Ningde's economic development February 1989 -- Both sides of Ningde's fiscal economy in the new situation March 1989 -- Opening up the economy of the she people April 1989 -- Forests are the key to Ningde's revitalization - thoughts on a strategic issue for economic development in Ningde January 1989 -- Strengthening the great unity of all ethnic groups - reflections on promoting the common prosperity of ethnic minorities June 1989 -- Real options for drafting and implementing an industrial policy July 1989 -- Breaking through difficulties - thoughts on developing township enterprises in poor areas October 1989 -- Let the people's congress play a bigger role in Ningde's development November 1989 -- Actively and steadily reform the communist youth league October 1989 -- Intellectual and cultural progress in impoverished areas December 1989 -- Enhancing our core strength on the front line for eliminating poverty - building rural party organizations January 1990 -- Developing a new resource - the transfer of surplus rural labor January 1990 -- How should we run education? February 1990 -- The path to developing big agriculture April 1990 -- Building collective economic strength in townships and villages to alleviate poverty April 1990 -- With one heart and one mind, the country and people will flourish - parting words for the leading officials of Ningde prefecture May 1990 -- Afterword
Keywords: China -- Politics and government; Democracy -- China